Ligand chemistry for surface functionalization in MXenes : A review - Jung, Sungmin; Zafar, Ujala; Achary, L. Satish Kumar; Koo, Chong Min (EcoMat (Beijing, China), 2023)
Surface chemistry of MXenes is of significant interest due to its potential to control their final optoelectronic and physicochemical properties, and address the oxidation and dispersion stabilities of MXenes. Surface chemistry of MXenes can be manipulated by either MXene synthesis via chemical etching or post surface functionalization method. Although numerous reviews have explored MXene synthesis methods, there has been a lack of focus on post surface functionalization. This review aims to fill this gap by summarizing recent advancements in the MXene surface functionalization chemistry, and elucidating mechanisms, properties, and future perspectives of functionalized MXenes. We discuss organic ligand molecules, such as organic salts, catechols, phosphonates, carboxylates, and silanes, which can be employed to surface‐functionalize MXene through covalent or non‐covalent bond interaction. This comprehensive review offers valuable insights for scientists and engineers in utilizing functionalized MXenes across diverse applications, including EMI shielding, energy storage, electronics, optoelectronics, and sensors. image